2010
DOI: 10.1063/1.3427585
|View full text |Cite
|
Sign up to set email alerts
|

A model for underpotential deposition in the presence of anions

Abstract: Lattice-gas model of nonadditive interacting particles on nanotube bundles J. Chem. Phys. 134, 064702 (2011); 10.1063/1.3530788 Critical behavior of interacting monomers adsorbed on one-dimensional channels arranged in a triangular crosssectional structure: Mixed interactions along and across the channels A simple model to study the effect of on top coadsorption of anions in underpotential deposition is formulated. It considers a lattice-gas model with pair potential interactions between nearest neighbors. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…In particular, the role of halide anions on the surface structure of UPD adatoms and the kinetics of metal deposition has received considerable attention. In addition, the role of halide anions in stabilizing UPD monolayers has been illustrated both by experimentalists [20,[45][46][47][48][49][50][51] and theoreticians alike [52][53][54]. Despite this interest, there has been little progress in understanding partial charge transfer at the electrochemical interface although it has been postulated that the adsorption of anions and, especially, partial charge transfer is strongly affected by the presence and strength of water adsorption at a given potential.…”
Section: The Underpotential Deposition Of Cu In the Presence Of Br Anmentioning
confidence: 99%
“…In particular, the role of halide anions on the surface structure of UPD adatoms and the kinetics of metal deposition has received considerable attention. In addition, the role of halide anions in stabilizing UPD monolayers has been illustrated both by experimentalists [20,[45][46][47][48][49][50][51] and theoreticians alike [52][53][54]. Despite this interest, there has been little progress in understanding partial charge transfer at the electrochemical interface although it has been postulated that the adsorption of anions and, especially, partial charge transfer is strongly affected by the presence and strength of water adsorption at a given potential.…”
Section: The Underpotential Deposition Of Cu In the Presence Of Br Anmentioning
confidence: 99%
“…Assuming that the movement of the electro-active solute is due only to diffusive process, he evaluated the current across the cell and showed that it decreases with the time according to 1= ffiffi t p . The model of Cottrell has been generalized recently by several authors for the technological importance of the electrodeposition technique [11][12][13][14][15][16][17][18][19][20][21]. In the standard approach the phenomenon related to the electrodeposition is described by means of a stochastic model, using an equation for the migration of the ions from the surface to the electrode (of diffusion type), and an equation describing their reaction on the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…8 First principles density functional theory (DFT) has been applied to obtain atomistic insights into the stability and structure of the metal monolayers achieving varying degrees of correspondence with experimental voltammetry. [9][10][11][12][13][14][15] These calculations are typically performed in the absence of a solvent; however, key features of the interface such as anion co-adsorption have been included when warranted, leading to enhanced descriptions of the interface. 14,15 Entropic effects have additionally been considered to obtain surface chemical potentials by including ideal configurational entropy or by fitting an Ising-like Hamiltonian to DFT results and subsequently performing grand canonical Monte Carlo calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] These calculations are typically performed in the absence of a solvent; however, key features of the interface such as anion co-adsorption have been included when warranted, leading to enhanced descriptions of the interface. 14,15 Entropic effects have additionally been considered to obtain surface chemical potentials by including ideal configurational entropy or by fitting an Ising-like Hamiltonian to DFT results and subsequently performing grand canonical Monte Carlo calculations. These approaches have been applied to study the UPD of hydrogen on platinum surfaces at finite temperatures, underscoring the importance of configurational entropy for modeling electrocapillary phenomena as well as the voltammetric response of electrodes in the presence of electrolytic environments.…”
Section: Introductionmentioning
confidence: 99%